2001
DOI: 10.1074/jbc.m008098200
|View full text |Cite
|
Sign up to set email alerts
|

Active (9.6 S) and Inactive (21 S) Oligomers of NHE3 in Microdomains of the Renal Brush Border

Abstract: We have previously shown that Na ؉ -H ؉ exchanger isoform NHE3 exists as both 9.6 and 21 S (megalin-associated) oligomers in the renal brush border (1). To characterize the oligomeric forms of the renal brush border Na ؉ -H ؉ exchanger in more detail, we performed membrane fractionation studies. We found that similar amounts of NHE3 were present in microvilli and a nonmicrovillar membrane domain of high density (dense vesicles). Horseradish peroxidase-labeled endosomes were not prevalent in the dense membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 37 publications
5
80
1
Order By: Relevance
“…LTA binds to specific glycoproteins present only in proximal tubule brush border (apical) membranes. 35,36 We demonstrate that AM fractions isolated with LTA were enriched with villin, validating the isolation of the outer brush border membrane fraction. Our results show that intrarenal administration of fenoldopam increased the quantity of AT 2 R protein in these AMs.…”
Section: Salomone Et Al D 1 and At 2 Receptor Interactions In Natriursupporting
confidence: 65%
“…LTA binds to specific glycoproteins present only in proximal tubule brush border (apical) membranes. 35,36 We demonstrate that AM fractions isolated with LTA were enriched with villin, validating the isolation of the outer brush border membrane fraction. Our results show that intrarenal administration of fenoldopam increased the quantity of AT 2 R protein in these AMs.…”
Section: Salomone Et Al D 1 and At 2 Receptor Interactions In Natriursupporting
confidence: 65%
“…We previously showed that 15-25% OptiPrep gradients separate dense membrane fractions enriched for markers of the intermicrovillar coated pit region of the brush border (Fig. 4, arrow) from other renal microsomes (34). Fig.…”
Section: ␥-Secretasementioning
confidence: 82%
“…COS-7 cells or renal microsomes isolated from mouse kidney cortex (19) were solubilized in sample buffer, and proteins were separated by SDS͞PAGE using 7.5% polyacrylamide gels according to Laemmli (20). For immunoblotting, proteins were transferred to poly(vinylidene difluoride) (PVDF, Immobilon-P, Millipore) with a Transphor transfer electrophoresis unit (Hoefer) and stained with Ponceau S in 0.5% trichloroacetic acid.…”
Section: Methodsmentioning
confidence: 99%